Sinoatrial block. Autonomic influences and clinical assessment. - Dighton, D H (1975)
Seventeen patient with sinoatrial block and 16 healthy volunteers were investigated with recently developed autonomic tests of atrial pacemaker function. Only one patients was found to be entirely normal in comparison with normal subjects, while another patients had supernormal responses. Fifteen patients had reduced responses relative to the controls implying impaired atrial pacemaker function or sinoatrial disease. It is suggested that while in some cases sinoatrial block may be of physiological origin, it is more often due to sinoatrial disease. The latter group are liable to Adams-Stokes syncope and may have additional atricventricular conduction abnormalities. The possible mechanisms and treatment of sinoatrial block are discussed relative to the autonomic and pacemaker function abnormalities described.